FINDING OUT THE FACTORS INFLUENCING BEHAVIOR OF CUSTOMERS FOR ESSENTIAL ITEMS IN THIS PARTIAL LOCKDOWN SITUATION - Das, Priyo (International Journal on Recent Trends in Business and Tourism (IJRTBT), 2021)
This present scenario of partial lockdown is quite different from the nationwide lockdown. Presently people basically have access to almost everything but they have to follow some rules and regulations as imposed by the Government of West Bengal. As a result, the behavior of customers will also be different from the past scenario, thus to find out this difference author had carried out this research to find out factors that influence the behavior of customers. For achieving this objective to make it more specific and to fill a gap, the author had used essential products. Data were collected by using the convenience sampling technique and before collecting data a pilot study was conducted to check the reliability of the data collection instrument. Data was collected from 225 respondents from Khardah, West Bengal, India. For finding out the factors, Exploratory Factor Analysis was used and 4 major factors had been identified and based on these factors, recommendations had been made which have practical implications.